New perspectives on computer concepts : includes interactive book-on-cd that contains the entire contents of the textbook, plus videos,software tours, course labs,computer-scored etc. - Parsons, June Jamrich; Oja, Dan. (Australia : Thompson Learning, 2000)
1. Computers. 2. Electronic Data Processing.
Includes index.
Keywords: Computers; Electronic data processing